(untitled) (Kronika Bydgoska, 2010)
Free of charge newspapers appeared in Bydgoszcz morę or less at the same time as throughout Poland, i.e. after 1989. At the beginning of the 1990’s, publishers in the city on the Brda River were pioneers of the establishment of a free information weekly, which would reach to most residents of the city. Unfortunately, these efforts finished with a failure due to Financial reasons. Only basing another project on“Express Media”resulted in a success. One can partially similarly assess the fate of cultural magazines, which sometimes ended their life after only several issues (e.g.“Grzecznie”,“Moment”,and“Mrówka”). The reason was similar - the lack of money. Periodicals that aim at advertising products and brands are doing much better. Whereas political magazines are successful owing to the power of the group they are to promote. However, the vicissitudes of life of free newspapers in Bydgoszcz and their significant number confirm that this is a developing market, which can surprise us many times.